Decoding tradition: culinary techniques and cultural significance in MSS 2926 - Kamal Baharin, Elisya Sopphilea; Ahmad Nizam, Nur Wafa Qadisah; Mohd Faharul, Farah Izatie; Azizan, Nur Ain Alia; Mohd Nordin, Nordiana (Universiti Teknologi MARA, Perak, 2025)
This paper investigates MSS 2926, diving into its complex content to reveal the intricate culinary arts of the ancient Malay community. The study applies rigorous philological analysis to reveal the rich culinary information hidden in MSS 2926, which includes categories such as cooking requirements, materials, methods, equipment, measures, and important recommendations. It also investigates the manuscript's linguistic influence, which is distinguished by a strong fusion of Arabic and regional Malay, illuminating its cultural and linguistic relevance. By deciphering the complexities of MSS 2926 Cooking Tips, this study contributes to a better understanding of ancient Malay culinary practices and their long-lasting influence on current culinary discourse. The purpose of this article is to chronicle and analyse the culinary expertise preserved in MSS 2926, throwing light on its cultural and historical importance within Malay culinary traditions. The issue addressed is a lack of comprehensive investigation into the detailed culinary practices and linguistic influences included in MSS 2926, which impedes a proper understanding of traditional Malay cuisine. Using document analysis, this paper conducts a thorough examination of MSS 2926 to extract and analyse culinary traditions, and cultural insights buried within the document. The findings reveal a wealth of culinary information in MSS 2926, including precise cooking procedures, ingredient selection criteria, and the cultural fusion of Arabic and Malay influences, all of which contribute to a better understanding of traditional Malay cuisine. This study emphasizes the value of MSS 2926 as a tangible cultural heritage, providing insights into historic Malay culinary practices that continue to affect current culinary arts and cultural identity. It emphasizes the significance of keeping and researching such documents to protect and preserve cultural heritage and culinary diversity.